2021
DOI: 10.1155/2021/6654220
|View full text |Cite
|
Sign up to set email alerts
|

Leukocytes from Patients with Drug-Sensitive and Multidrug-Resistant Tuberculosis Exhibit Distinctive Profiles of Chemokine Receptor Expression and Migration Capacity

Abstract: Tuberculosis (TB), caused by Mycobacterium tuberculosis (Mtb), remains as a leading infectious cause of death worldwide. The increasing number of multidrug-resistant TB (MDR-TB) cases contributes to the poor control of the TB epidemic. Currently, little is known about the immunological requirements of protective responses against MDR-TB. This is of major relevance to identify immune markers for treatment monitoring and targets for adjuvant immunotherapies. Here, we hypothesized that MDR-TB patients display uni… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
18
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 16 publications
(18 citation statements)
references
References 55 publications
0
18
0
Order By: Relevance
“…The frequency of CD3 + myeloid cells has been reported to be increased upon mycobacterial infections [ 7 , 8 , 9 ]. Therefore, to evaluate the effect of Mtb virulence on the induction of these subpopulations, MDMs were infected with H37Ra (multiplicity of infection (MOI) = 1 and 10) and H37Rv (MOI = 1 and 5) for a short time (24 h).…”
Section: Resultsmentioning
confidence: 99%
See 4 more Smart Citations
“…The frequency of CD3 + myeloid cells has been reported to be increased upon mycobacterial infections [ 7 , 8 , 9 ]. Therefore, to evaluate the effect of Mtb virulence on the induction of these subpopulations, MDMs were infected with H37Ra (multiplicity of infection (MOI) = 1 and 10) and H37Rv (MOI = 1 and 5) for a short time (24 h).…”
Section: Resultsmentioning
confidence: 99%
“…The activation of the chemokine/chemokine receptor axis is one of the most important processes in the regulation of cell migration [ 18 ]. Recently, we reported that CD3 + monocytes from patients with TB poorly express CCR2; nevertheless, they are able to migrate in response to IP-10 stimuli [ 9 ]. Therefore, the expression of CCR2, CXCR1, and CCR7 chemokine receptors inside the gate of CD3 − , CD3 + TCRαβ + , and CD3 + TCRαβ − MDMs was evaluated by flow cytometry, and that of CCL2 (ligand to CCR2), IL-8 (ligand to CXCR1), and CCL19 (ligand to CCR7) was evaluated in the culture supernatant by ELISA.…”
Section: Resultsmentioning
confidence: 99%
See 3 more Smart Citations